Agenda on cooperatives for development cooperation in Tanzania. Issue 2 (December 2015) - Sumelius, John; Tenaw, Shimlles; Bee, Faustine K.; Chambo, Suleman
Highlights: Effective functioning of cooperatives in Tanzania is characterized by strong primary cooperative societies where the members have control of the cooperative. Financial services are close to the members of the primary society. Members are trained to know their rights, to know how to run a cooperative efficiently, to maintain their autonomy and independence from external pressure. The secondary structure is light and mainly provides relevant information to the members and carries out business negotiations with both foreign and domestic buyers. The secondary structure does not deal with any money or physical commodities directly. Activities carried out by the secondary cooperatives are transparent. The partnership between the cooperative and the foreign investor is based on that between cooperatives themselves.